Candidate Predictors of Health-Related Quality of Life of Colorectal Cancer Survivors: A Systematic Review. (24th February 2016) - Bours, Martijn J.L.; Linden, Bernadette W.A.; Winkels, Renate M.; Duijnhoven, Fränzel J.; Mols, Floortje; Roekel, Eline H.; Kampman, Ellen; Beijer, Sandra; Weijenberg, Matty P.
Abstract: The population of colorectal cancer (CRC) survivors is growing and many survivors experience deteriorated health-related quality of life (HRQoL) in both early and late post-treatment phases. Identification of CRC survivors at risk for HRQoL deterioration can be improved by using prediction models. However, such models are currently not available for oncology practice. As a starting point for developing prediction models of HRQoL for CRC survivors, a comprehensive overview of potential candidate HRQoL predictors is necessary. Therefore, a systematic literature review was conducted to identify candidate predictors of HRQoL of CRC survivors. Original research articles on associations of biopsychosocial factors with HRQoL of CRC survivors were searched in PubMed, Embase, and Google Scholar. Two independent reviewers assessed eligibility and selected articles for inclusion ( N = 53). Strength of evidence for candidate HRQoL predictors was graded according to predefined methodological criteria. The World Health Organization's International Classification of Functioning, Disability and Health (ICF) was used to develop a biopsychosocial framework in which identified candidate HRQoL predictors were mapped across the main domains of the ICF: health condition, body structures and functions, activities, participation, and personal and environmental factors. The developed biopsychosocial ICF framework serves as a basis for selecting candidate HRQoL predictors, thereby providing conceptual guidance for developing comprehensive, evidence-based prediction models of HRQoL for CRC survivors. Such models are useful in clinical oncology practice to aid in identifying individual CRC survivors at risk for HRQoL deterioration and could also provide potential targets for a biopsychosocial intervention aimed at safeguarding the HRQoL of at-risk individuals. Abstract : A systematic literature review was conducted to identify candidate predictors of health-related quality of life (HRQoL) of colorectal cancer (CRC) survivors that could be used to develop prediction models of HRQoL deterioration. A model of HRQoL was developed based on the biopsychosocial framework of the International Classification of Functioning, Disability and Health, which serves as a basis for selecting candidate HRQoL predictors and thereby provides conceptual guidance for developing comprehensive, evidence-based prediction models of HRQoL for CRC survivors.